Pengaruh Jurusan Asal Sekolah Terhadap Motivasi Belajar Matematika Mahasiswa Menggunakan Model Pembelajaran SAVI - Pupung SR; Sodikin Sodikin; Isnani Agriandita (LPPM Institut Teknologi Petroleum Balongan, 2022)
The aims of this study were to (1) analyze the differences in student learning motivation using the SAVI learning model and those using the expository learning model, (2) to analyze the differences in student learning motivation using the SAVI learning model and those using the expository learning model in terms of school majors. This study is an experimental study using a Mix Method approach involving 68 students of the Akamigas Balongan Indramayu Petroleum Engineering Study Program. The sampling technique used was Simple Random Sampling, two classes were selected as samples, namely class 20 TPA as experimental class I and class 20 TPB as experimental class II. The tools or instruments in this study were learning outcomes tests in the form of explanations about explanations, interviews, motivation questionnaires and questionnaires from school majors. The data analysis of this research is using the mean comparison test, ANOVA test and correlation test. The results of this study are: (1) the learning motivation of students who use the SAVI learning model is better than those using the expository learning model, (2) the learning motivation of students who use the SAVI model and come from the origin of the science department is better. Thus, the SAVI learning model is good for use in learning mathematics because students are more active and interested in learning and can be a reference for teachers/lecturers in increasing students learning motivation.